Tuning the selectivity of CO2 hydrogenation using ceramic hollow fiber catalytic modules - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Kharul, Ulhas K.; Naidu, V. Satyam; Devi, R. Nandini (Reaction Chemistry & Engineering, 2021)
The unique structural features and advantageous pore distributions of alumina hollow fibers can be exploited to tune the selectivity in heterogeneous catalysis. Formation of a finger-like cavity structure is the unique characteristic of the phase inversion method, which provides a larger surface area to volume ratio desirable for catalytic reactions. This feature, along with a highly porous sandwiched skin layer, makes this architecture superior to conventional powder catalysts or other structured catalyst forms like monoliths. Alumina hollow fibers are prepared by the modified phase inversion method and characterized for their pore size and distribution. Ni metal nanoparticles are uniformly deposited in the Al2O3 hollow fibers to prepare a Ni/Al2O3 catalyst and tested for the CO2 methanation reaction. Suitable reactor and catalyst loading methods are designed and optimized to achieve higher CO2 to methane conversion in a temperature range of 225 to 400 degrees C. The alpha-alumina phase, which is usually reported to be a poor support for Ni in CO2 methanation in the conventional fixed bed configuration, showed high activity when modulated as hollow fibers. Also, the selectivity to CH4 is enhanced and minimal CO formation is observed. The kinetic rate expressions are simulated for the prediction of methane and CO gas evolution at the outlet with temperature. The experimental results for the gas composition are in good agreement with the model predictions. The advantage of such a module reactor is explained based on the mass transfer limitations and consequently the reaction time constants arrived at from the predicted gas compositions.

Trap inlaid cationic hybrid composite material for efficient segregation of toxic chemicals from water - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2022)
Metal-based oxoanions are potentially toxic pollutants that can cause serious water pollution. Therefore, the segregation of such species has recently received significant research attention. Even though several adsorbents have been employed for effective management of chemicals, their limited microporous nature along with non-monolithic applicability has thwarted their large-scale real-time application. Herein, we developed a unique anion exchangeable hybrid composite aerogel material (IPcomp-6), integrating a stable cationic metal-organic polyhedron with a hierarchically porous metal-organic gel. The composite scavenger demonstrated a highly selective and very fast segregation efficiency for various hazardous oxoanions such as, HAsO42-, SeO42-, ReO4-, CrO42-, MnO4-, in water, in the presence of 100-fold excess of other coexisting anions. The material was able to selectively eliminate trace HAsO42- even at low concentration to well below the As-v limit in drinking water defined by WHO.
Keywords: Aerogel; Chemical Separation; Hybrid composite; Metal-Organic Gel; Metal-Organic Polyhedra

Trap inlaid cationic hybrid composite material for efficient segregation of toxic chemicals from water (vol 61, e202203385, 2022) - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2022)

Thrombin immobilized hemocompatible radiopaque polyurethane microspheres for topical blood coagulation - Naik, Sonali S.; Torris, Arun; Ghuge, Gorakh Hiraman; Karthika, V. K.; Joseph, Roy; Nair, Kiran Sukumaran (JOURNAL OF BIOMEDICAL MATERIALS RESEARCH PART A, 2025)
Keywords: ALGINATE MICROSPHERES; ENDOVASCULAR TREATMENT; PRECISE LOCALIZATION